2018
DOI: 10.1590/2317-1782/20182017216
|View full text |Cite
|
Sign up to set email alerts
|

O gênero e a idade influenciam as dimensões do palato duro? Revisão sistemática da literatura

Abstract: RESUMO Objetivo Analisar a influência do gênero e da idade nas dimensões do palato duro, bem como verificar os parâmetros de referência disponíveis na literatura. Estratégia de pesquisa Dois examinadores realizaram a pesquisa de forma independente nas bases de dados Cochrane Library, PubMed-Medline e Web of Knowledge utilizando os descritores de acordo com as regras de sintaxe de cada banco de dados. Critérios de seleção Estudos em humanos observacionais ou experimentais, que avaliaram as dimensões do pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…In addition to that, a systematic review was carried out to investigate the gender effect on palatal dimensions. The outcome of that review was in line with our results [26]. This harmony between our findings and previously published reports provides validity to our experimental design.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to that, a systematic review was carried out to investigate the gender effect on palatal dimensions. The outcome of that review was in line with our results [26]. This harmony between our findings and previously published reports provides validity to our experimental design.…”
Section: Discussionsupporting
confidence: 92%
“…It was found that sex and facial type influence the dimensions of the hard palate, and there was an association between the measurements of the About the morphometric analysis of the hard palate, significant differences were found between sexes, and among the facial types, for some measurements. Males had greater width of the hard palate at the first molars region, and greater values of height of the hard palate at the first premolars region, corroborating previous studies [20,21]. For facial types, in general, dolichocephalic individuals presented greater height of the hard palate in the first premolars and molars regions, whereas brachycephalic patients had greater width of the hard palate in the first premolars region.…”
Section: Discussionsupporting
confidence: 88%
“…Males had greater width of the hard palate at the rst molars region, and greater values of height of the hard palate at the rst premolars region, corroborating previous studies. 19,20 For facial types, in general, dolichocephalic individuals presented greater height of the hard palate in the rst premolars and molars regions, whereas brachycephalic patients had greater width of the hard palate in the rst premolars region. In view of this result, it is possible to observe the in uence of the vertical growth trend in the shape of the hard palate, since the greater vertical tendency of growth (dolichocephalic) presented greater height of the hard palate, while the greater horizontal tendency (brachycephalic) showed greater width of the hard palate.…”
Section: Discussionmentioning
confidence: 99%